2014
DOI: 10.1016/j.neuropharm.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

When a good taste turns bad: Neural mechanisms underlying the emergence of negative affect and associated natural reward devaluation by cocaine

Abstract: An important feature of cocaine addiction in humans is the emergence of negative affect (e.g., dysphoria, irritability, anhedonia), postulated to play a key role in craving and relapse. Indeed, the DSM-IV recognizes that social, occupational and/or recreational activities become reduced as a consequence of repeated drug use where previously rewarding experiences (e.g., food, job, family) become devalued as the addict continues to seek and use drug despite serious negative consequences. Here, research in the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 105 publications
(138 reference statements)
4
37
0
Order By: Relevance
“…In contrast, lateral habenula neurons make synaptic connections on both GABAergic neurons in the RMTg as well as DA neurons projecting to PFC (Omelchenko and Sesack, 2005;BalcitaPedicino et al, 2011;Lammel et al, 2012). Importantly, optical stimulation of lateral habenula terminals in the VTA induced inhibitory postsynaptic currents in VTA DA neurons projecting to NAc lateral shell (Lammel et al, 2012), which supports the idea that VTA DA neurons are tonically inhibited by RMTg GABAergic neurons (Bourdy and Barrot, 2012). These findings show that VTA neurons are part of segregated circuits that control reward-and aversion-associated behaviors.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In contrast, lateral habenula neurons make synaptic connections on both GABAergic neurons in the RMTg as well as DA neurons projecting to PFC (Omelchenko and Sesack, 2005;BalcitaPedicino et al, 2011;Lammel et al, 2012). Importantly, optical stimulation of lateral habenula terminals in the VTA induced inhibitory postsynaptic currents in VTA DA neurons projecting to NAc lateral shell (Lammel et al, 2012), which supports the idea that VTA DA neurons are tonically inhibited by RMTg GABAergic neurons (Bourdy and Barrot, 2012). These findings show that VTA neurons are part of segregated circuits that control reward-and aversion-associated behaviors.…”
Section: Introductionmentioning
confidence: 76%
“…Measurements in awake and behaving rats have revealed that brief (ϳ1-2 s) DA release events (ϳ25-100 nM), commonly referred to as dopamine transients, occur spontaneously with low probability (Owesson-White et al, 2012). Rewarding stimuli, including food Brown et al, 2011;McCutcheon et al, 2012), drugs of abuse Aragona et al, 2009), and cues that predict their delivery (Phillips et al, 2003;Daberkow et al, 2013), increase the probability of dopamine transients at their onset. Intraoral infusions of a rewarding sucrose solution also increase dopamine transients within the dorsomedial shell of the NAc that are time-locked to infusion onset, as well as throughout and after the intraoral infusion ).…”
Section: Mesolimbic Encoding Of Rewarding and Aversive Stimulimentioning
confidence: 99%
See 3 more Smart Citations